1986
DOI: 10.1136/jcp.39.7.779
|View full text |Cite
|
Sign up to set email alerts
|

Improved serodiagnosis of tuberculosis using two assay test.

Abstract: SUMMARY An antigen capture immunoassay was developed for the detection of mycobacterial antigens in sera from patients with tuberculosis. The assay was evaluated together with an antibody measuring enzyme immunoassay in a clinical trial for serodiagnosis of tuberculosis.Sensitivity of the antibody assay for active pulmonary tuberculosis, including relapsed infections, was 75%, and specificity with other lung diseases was 97%. Sensitivity for extrapulmonary tuberculosis was 84-5% and specificity 84%. Sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Preliminary results have been published on new diagnostic tests for tuberculosis based on detection of mycobacterial antigens in cerebrospinal fluid (10,13), serum (11,14), and sputum (4,22). The authors reported sensitivity rates of 45 to 88% and specificity rates of 91 to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results have been published on new diagnostic tests for tuberculosis based on detection of mycobacterial antigens in cerebrospinal fluid (10,13), serum (11,14), and sputum (4,22). The authors reported sensitivity rates of 45 to 88% and specificity rates of 91 to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Although ELISA may not confirm active tuberculosis infection in these samples it is definitely helpful in discriminating between the persons with tuberculosis infection and those with other infections. To recognise mycobacterial infection with high predictability, two assay tests one detecting antigen the other antibodies in the same clinical sample have been proposed [18]. However, in our study a single assay detecting IgG antibodies showed quite promising operational validity with 93% sensitivity and 100% specificity which are comparable to the two-assay tests [18].…”
Section: Discussionmentioning
confidence: 64%
“…To recognise mycobacterial infection with high predictability, two assay tests one detecting antigen the other antibodies in the same clinical sample have been proposed [18]. However, in our study a single assay detecting IgG antibodies showed quite promising operational validity with 93% sensitivity and 100% specificity which are comparable to the two-assay tests [18]. Polyclonal antisera that can be used for detecting mycobacterial infection have been documented [29].…”
Section: Discussionmentioning
confidence: 73%
“…The problem of the immune complex must also be solved in order to decrease the false negatives. It is likely that future tests will include assays for both antigens from and antibodies against the tuberculous organism [20]. Monoclonal antibodies will remain important in many respects: for the purification of specific antigens, for competitive inhibition tests, or for antigen capturing assays.…”
Section: Ridell*mentioning
confidence: 99%